Domestic Captivity and the British Subject, 1660-1750 - Ingrassia, Catherine (Book collections on Project MUSE., 2022)
"This book considers fictional texts by British authors from the Restoration and first half of the eighteenth century in which captivity centrally informs identity, actions, or human relationships for white British subjects. The exercise of institutional and personal power could create conditions in which those least empowered, particularly women, perceived themselves to be captive subjects. This "domestic captivity" is intimately connected to England's substantial involvement in the systematic enslavement of kidnapped Africans, even as early fictional narratives ignore the experience of enslaved people. The book looks at canonical authors such as Aphra Behn, Richard Steele, and Eliza Haywood, as well as popular writers such as Penelope Aubin and Edward Kimber"--